1987
DOI: 10.1002/ajpa.1330730102
|View full text |Cite
|
Sign up to set email alerts
|

Blood types of the native Americans of Oklahoma

Abstract: Large numbers of Indians from Oklahoma were screened for a variety of red cell antigens. Sufficient numbers of Cherokees, Creeks, and Choctaws were studied to calculate gene frequencies. These tribes originated in the Southeastern United States and were forcibly moved to Oklahoma. The Creeks and Choctaws have not been studied previously. A small number of Cherokees remained in North Carolina, and their blood types have been reported. The blood types of the Oklahoma Cherokees are quite similar to those observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1993
1993
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…In addition, as pointed out in Subjects and Methods, the Mvskoke have a long history of contact and admixture with European and African Americans. Blood group data reported for them by Kasprisin et al (1987) identified markers indicative of African (4% of ABO*B) and Caucasian (1% of KELL*K) ancestry. Mitochondrial DNA analyses showed in both groups Amerindian haplogroups only (Merriwether et al, 1994(Merriwether et al, , 1995Bailliet et al, 1994), which is not surprising.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…In addition, as pointed out in Subjects and Methods, the Mvskoke have a long history of contact and admixture with European and African Americans. Blood group data reported for them by Kasprisin et al (1987) identified markers indicative of African (4% of ABO*B) and Caucasian (1% of KELL*K) ancestry. Mitochondrial DNA analyses showed in both groups Amerindian haplogroups only (Merriwether et al, 1994(Merriwether et al, , 1995Bailliet et al, 1994), which is not surprising.…”
Section: Resultsmentioning
confidence: 98%
“…Their language is classified by Greenberg (1987) as belonging to the Muskogean subdivision of the Yuki-Gulf, which in turn belongs to the Penutian stock. They moved to Oklahoma about 150 years ago, and at present live in several rural communities (details in Kasprisin et al, 1987).…”
Section: Subjectsmentioning
confidence: 99%
“…Several mtDNA studies have revealed low levels of European maternal gene flow into North American Indian populations in the form of West Eurasian haplogroup H, J, and K mtDNAs (Scozzari et al 1997, Torroni et al 1993a). Evidence of European paternal gene flow has also been seen in studies of blood group markers and NRY variation in these populations (Bolnick 2004, Huoponen et al 1997, Kaspirin et al 1987, Pollitzer et al 1962. In fact, nearly 60% of Greenlandic Inuit Y chromosomes may have European origins, with these most likely coming from Norse settlers who were assimilated into Inuit groups some 500 years ago .…”
Section: Post-contact Americasmentioning
confidence: 85%
“…Their remote position below the regression line (i.e., below the expected heterozygosity) gives credence to the notion of the Waorani being one of the Native American groups less impacted by gene flow processes. In contrast, the Mvskoke, which have been reported to have experienced a substantial degree of admixture with nonAmerican native groups (Kasprisin et al, 1987;Novick et al, 1998), appeared with gene flow levels far above the average.…”
Section: Discussionmentioning
confidence: 74%